Short- and long-term mortality of subarachnoid hemorrhage according to hospital volume and severity using a nationwide multicenter registry study - Park, Sang-Won; Lee, Ji Young; Heo, Nam Hun; Han, James Jisu; Lee, Eun Chae; Hong, Dong-Yong; Lee, Dong-Hun; Lee, Man Ryul; Oh, Jae Sang (Frontiers in Neurology, 2022)
Introduction Recent improvements in treatment for subarachnoid hemorrhage (SAH) have decreased the mortality rates; however, the outcomes of SAH management are dependent on many other factors. In this study, we used nationwide, large-scale, observational data to investigate short- and long-term mortality rates after SAH treatment and the influence of patient severity and hospital volume. Patients and methods We selected patients with SAH treated with clipping and coiling from the South Korean Acute Stroke Assessment Registry. High- and low-volume hospitals performed ≥20 clipping and coiling procedures and <20 clipping and coiling procedures per year, respectively. Short- and long-term mortality were tracked using data from the Health Insurance Review and Assessment Service. Results Among 2,634 patients treated using clipping and coiling, 1,544 (58.6%) and 1,090 (41.4%) were hospitalized in high- and low-volume hospitals, respectively, and 910 (34.5%) and 1,724 (65.5%) were treated with clipping and coiling, respectively. Mortality rates were 13.5, 14.4, 15.2, and 16.1% at 3 months, 1, 2, and 4 years, respectively. High-volume hospitals had a significantly lower 3-month mortality rate. Patients with mild clinical status had a significantly lower 3-month mortality rate in high-volume hospitals than in low-volume hospitals. Patients with severe clinical status had significantly lower 1- and 2-year mortality rates in high-volume hospitals than in low-volume hospitals. Conclusion Short- and long-term mortality in patients with SAH differed according to hospital volume. In the modern endovascular era, clipping and coiling can lead to better outcomes in facilities with high stroke-care capabilities.